The tra region of the nopaline-type Ti plasmid is a chimera with elements related to the transfer systems of RSF1010, RP4, and F. - Farrand, S K (1996)
The Ti plasmids of Agrobacterium tumefaciens encode two transfer systems. One mediates the translocation of the T-DNA from the bacterium to a plant cell, while the other is responsible for the conjugal transfer of the entire Ti plasmid from one bacterium to another. The determinants responsible for conjugal transfer map to two regions, tra and trb, of the nopaline-type Ti plasmid pTiC58. By using transposon mutagenesis with Tn3HoHo1, we localized the tra determinants to an 8.5-kb region that also contains the oriT region. Fusions to lacZ formed by transposon insertions indicated that this region is expressed as two divergently transcribed units. We determined the complete nucleotide sequence of an 8,755-bp region of the Ti plasmid encompassing the transposon insertions defining tra. The region contains six identifiable genes organized as two units divergently transcribable from a 258-bp inter-genic region that contains the oriT site. One unit encodes traA, traF, and traB, while the second encodes traC, traD, and traG. Reporter insertions located downstream of both sets of genes did not affect conjugation but were expressed, suggesting that the two units encode additional genes that are not involved in transfer under the conditions tested. Proteins of the predicted sizes were expressible from traA, traC, traD, and traG. The products of several Ti plasmid tra genes are related to those of other conjugation systems. The 127-kDa protein expressed from traA contains domains related to MobA of RSF1O1O and to the helicase domain of TraI of plasmid F. The translation product of traF is related to TraF of RP4, and that of traG is related to TraG of RP4 and to VirD4 of the Ti plasmid T-DNA transfer system. Genetic analysis indicated that at least traG and traF are essential for conjugal transfer, while sequence analysis predicts that traA also encodes an essential function. traB, while not essential, is required for maximum frequency of transfer. Patterns of sequence relatedness indicate that the oriT and the predicted cognate site-specific endonuclease encoded by traA share lineage with those of the transfer systems of RSF1010 and plasmid F, while genes of the Ti plasmid encoding other essential tra functions share common ancestry with genes of the RP4 conjugation system.